Respon Anatomi dan Fisiologi Akar Kedelai terhadap Cekaman Kekeringan - Rosawanti, Pienyani; Ghulamahdi, Munif; Khumaida, Nurul (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2015)
ABSTRACTDrought stress in crop occurs due to imbalance between demand and supply of water. Crop responses to drought stress depend on their genotypes. Drought stress causes anatomical changes and root damage. The objective of this research was to study the effect of drought stress on anatomy and physiology of soybean root. The research was conducted at Laboratory of Microtechnique, Department of Agronomy and Horticulture, Bogor Agricultural University in November 2013. A Completely Randomized Design with two factors was used in the research i.e. soybean genotypes (Wilis, PG 57-1, SC 39-1) and PEG (0, 20%) with three replications. The result showed that genotype and PEG affected the size of the cortex, stele, and xylem. PG 57-1 genotype showed the decrease of cortical thickness, diameter of stele and the diameter of xylem, on the other hand, in SC 39-1, there was an increase. Drought stress (PEG 20%) could also cause damage to the root membrane as indicated by the occurrence of lipid peroxides. Wilis and PG 57-1 were tolerant while SC 39-1 was sensitive to drought stress.Keywords:cortex, lipid peroxides, PEG, Schiff’s reagent, xylem